A British national observatory: the building of the New Physical Observatory at Greenwich, 1889–1898. Issue 4 (December 2014) - HIGGITT, REBEKAH
Abstract Over its long history, the buildings of the Royal Observatory in Greenwich were enlarged and altered many times, reflecting changing needs and expectations of astronomers and funders, but also the constraints of a limited site and small budgets. The most significant expansion took place in the late nineteenth century, overseen by the eighth Astronomer Royal, William Christie, a programme that is put in the context of changing attitudes toward scientific funding, Christie's ambitious plans for the work and staffing of the Observatory and his desire to develop a national institution that could stand with more recently founded European and American rivals. Examination of the archives reveals the range of strategies Christie was required to use to acquire consent and financial backing from the Admiralty, as well as his opportunistic approach. While hindsight might lead to criticism of his decisions, Christie eventually succeeded in completing a large building – the New Physical Observatory – that, in its decoration, celebrated Greenwich's past while, in its name, style, structure and contents, it was intended to signal the institution's modernization and future promise.